Last child in the woods : saving our children from nature-deficit disorder - Louv, Richard (Algonquin Books of Chapel Hill, 2008)
Louv talks with parents, children, teachers, scientists, religious leaders, child-development researchers, and environmentalists to find ways for children to experience the natural world more deeply.